Evaluation of common liver masses and clinical and operative findings in a dog - Durmuş, Ali Said; Polat, Eren (Kastamonu Üniversitesi, 2023)
In this case report, it was aimed to evaluate the clinical, laboratory and operative findings of liver masses encountered in a 13-year-old Golden Retriever dog. It was determined that the dog who presented with complaints of difficulty in walking and swelling in the abdominal region had an excessive swelling in the abdominal region and an asymmetrical appearance. It was determined that hematocrit (HCT), red blood cells count (RBC) and hemoglobin level (HGB) decreased significantly, while alanine aminotransferase (ALT) activity increased critically. The radiographic and ultrasonographic examination of the abdomen, it was determined that the internal organs were not visible and abnormal fluid was accumulated. An experimental laparotomy was performed. During the operation, tumor-like masses in different sizes were determined on the liver lobes. In the postoperative period, the patient was euthanized at the request of the owner, due to the worsening of the patient's health condition and the recurrence of abdominal distension.
Keywords: Veterinary Surgery; Veteriner Cerrahi